معركة أُقليش ودورها في الجهاد الإسلامي بالأندلس 501هـ-1108م - حموم, خالد (جامعة الوادي University of Eloued, 2017)
سلك الأمير علي بن يوسف بعد توليه أمر المرابطين طريق أبيه يوسف بن تاشفين في أموره كلها، خاصةً فيما يتعلق بالجهاد في سبيل الله وردِّ حركة الاسترداد المسيحي للأندلس، ولأجل ذلك بادر بالجواز إلى الأندلس مباشرةً بعد توليه شأن المرابطين سنة 500هـ/1106م، فكلَّف أخاه تميم بخوض معركة فاصلة ضدَّ النَّصارى الصَّليبيِّين بشرق الأندلس حيث توجد مدينة أُقليش، وقد أسفرت هذه المعركة على انتصار باهر للمرابطين، حيث تمَّ فتح أُقليش في شوال 501هـ/ماي 1108م وهزم القوَّات القشتاليَّة بقيادة سانشو الابن الوحيد لألفونسو السَّادس وولي عهده الذي قُتل في المعركة مع سبعة من كبار قادته والكثير من جنده. After the death of Youcef ben tachfin the prance of Almorabitin, his san Ali ben youcef continue in the Sam strategy as his father was doing in all domanins especially fighting the enemies of Islam and protected the Andalusia from Christian movement, in the year of 500 ah/1106 ad he decided to centralize in Andalusia, whan he give his brother Temim the responsibility of fighting agents the Christian in the east of Andalusia exactly the town of Uclés they entered it, he made a grat victory he killed Sancho the commander of Castilian army, the only son of Alphonse VI and his crown prince with seven leaders and many of his soldiers’ in chawal 501 ah/may 1108 ad.
Keywords: المرابطين، الأندلس، أُقليش، حركة الاسترداد المسيحي، علي بن يوسف، ألفونسو السَّادس